Genetic estimates of reproduction and production traits in Mehsana buffalo - Galsar, Nirali S.; Shah, Ramesh R.; Gupta, Jay Prakash; Pandey, Dinesh P.; Prajapati, K. B.; Patel, Jetha B. (Indian Journal of Dairy Science, 2016)
The data pertaining to variable production and reproduction traits of Mehsana buffaloes (812 lactation production records of 285 buffaloes) were collected from Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar to obtain the genetic parameters of various production and reproduction traits in Mehsana buffaloes. The least squares means of various production and reproduction traits were adjusted for significant non-genetic factors and from these adjusted data, genetic parameters viz., heritability estimates, repeatability estimates as well as genetic and phenotypic correlations were estimated. Among the production traits, lactation yield and days to attain peak yield had moderate and highly significant (P≤0.01) heritability estimate whereas others had low and non-significant estimates. Highly significant but low repeatability estimates were obtained for lactation yield, lactation length and days to attain peak yield whereas moderate repeatability estimate was obtained for peak yield. Further, the genetic correlations of peak yield with lactation yield and days to attain peak yield and the phenotypic correlations of lactation yield with lactation length were highly significant (P≤0.01). Similarly, among the reproduction traits, dry period, service period and calving interval had low and non-significant heritability estimates, whereas age at first service and age at first calving had heritability estimates that were beyond the theoretical limits. Further, lower repeatability estimates were observed for all reproduction traits under study. In addition to this, genetic and phenotypic correlations of calving interval with dry period and service period and phenotypic correlations of dry period with service period and that of age at first calving with age at first service were highly significant (P≤0.01).